Pengaruh Gender Diversity, Agresivitas Pajak, dan Green Accouting Terhadap Corporate Social Responsibility : (Studi Kasus pada Perusahaan Sektor Energi Yang Terdaftar di BEI 2018-2021) - Galuh Candra Kusuma; Desy Nur Prastiwi; LMS Kristiyanti (Nur Science Institute, 2023)
This study aims to examines the influence of gender diversity, tax aggressiveness, and green accounting on corporate social responsibility (CSR) during 2018-2021. This study is a type of quantitative research with the research method used descriptive statistic. This study used secondary data on company listed on the BEI. The total sample used in this study was 80 companies based on purposive sampling criteria. The analysis technique used is multiple linear regression. The result shows the gender diversity, tax aggressiveness, and green accounting have a significant effect simultaneously on corporate social responsibility. partially the gender diversity and green accounting have significant effect on corporate social responsibility, while tax aggressiveness have no significant effect on corporate social responsibility